Analysis of the Stability of Reinforced Plastic Waste Treated Clay as Embankment Fill on Soft Soils - Shelema Amena (Advances in Civil Engineering)
The purpose of this study is to analyze the suitability and stability of clay soil treated with plastic waste as an embankment fill. Plastic wastes are used to stabilize the locally found weak clay. The locally found weak clay soil is stabilized with plastic waste. The stability analyses of the proposed slope have been done by finite element method using geotechnical software PLAXIS 2D. The stability analyses were performed for different conditions considering the geometry of the embankment, characterization of fill material, and the strength of reinforcement. Different models were analyzed to determine the safe height, side slope, and tensile strength of geogrid required to stabilize the embankment in addition to that of unreinforced embankments. The factor of safety of each trial is taken to check the stability of the modeled embankments. Accordingly, the factor of safety increases as geogrid axial stiffness increases greater than 500 kN/m. The analysis results revealed that with increasing slope height and slope angle the factor of safety decreases. This study found that plastic waste treated clay could be used as embankment fill when reinforced with geogrid.